(untitled) (Third Sector Social Economic Review, 2023)
Abstract The worldwide Covid-19 pandemic has caused disruptions in production and supply chains. This process had a negative impact on the Turkish economy, and double-digit rates began to be seen. As inflation has many negative effects on economies, it also negatively affected the transfer of accurate information, which is one of the most basic functions of financial statements. Inflation corrections and inflation accounting came to the fore again in order to eliminate these negative effects of inflation experienced in Turkey on the financial statements. In the study, it was investigated whether the expenditure affects the cost or not. In this direction, the basic financial statements of the textile enterprises traded in the BIST for 2021 were used. Values in the financial statements have been corrected for inflation using the General Price-Current Value (Substitution) Cost Method. The main account items in the balance sheet and income statement are classified as monetary and non-monetary values. The new values are calculated by multiplying the non-monetary values with the inflation correction coefficient found according to the Domestic Producer Price Index (D-PPI) data published by the Turkish Statistical Institute. The financial ratios of these enterprises were calculated separately before and after inflation correction. It has been determined that there is a positive increase in the financial ratios used compared to the before correction. With these ratios, the performance ranking of the enterprises was made with TOPSIS, one of the Multi-Criteria Decision Making (MCDM) methods. As a result, it was observed that inflation adjustments changed the performance ranking.